Dosing to rash? – The role of erlotinib metabolic ratio from patient serum in the search of predictive biomarkers for EGFR inhibitor-mediated skin rash. (March 2016) - Steffens, Michael; Paul, Tanusree; Hichert, Vivien; Scholl, Catharina; von Mallek, Dirk; Stelzer, Christoph; Sörgel, Fritz; Reiser, Bärbel; Schumann, Christian; Rüdiger, Stefan; Boeck, Stefan; Heinemann, Volker; et al.
Abstract: Aim: The aim of this study was to investigate if biomarkers of individual drug metabolism, respectively, the erlotinib/O-desmethyl-erlotinib metabolic ratio, may be a predictive factor for the severity of erlotinib-mediated skin rash in epidermal growth factor receptor (EGFR) inhibitor-treated patients suffering from epithelial cancers. This is especially important since it is known that the severity of skin rash has a prognostic value on outcome and survival in cancer patients experiencing skin rash under treatment with EGFR inhibitors. Methods: From 2008 to 2014, 96 patients, n = 63 suffering from histologically confirmed non-small-cell lung cancer and n = 33 from pancreatic adenocarcinoma were observed for the occurrence and severity of skin rash after the onset of treatment with erlotinib. The primary end-points (occurrence and severity of skin rash, progression-free survival [PFS] and overall survival [OS]) were analysed with regard to erlotinib and its metabolite O-desmethyl-erlotinib trough serum concentrations measured at 4 weeks after onset of therapy by the use of correlation, multiple regression and survival analysis. Results: Occurrence of skin rash was associated with PFS (p = 0.0042) and OS (p = 0.017) in the overall cohort of erlotinib-treated cancer patients. Drug-metabolising activity assessed by the erlotinib/O-desmethyl-erlotinib metabolic ratio was correlated with severity of skin rash (p = 0.023) and as well highly associated with both PFS (p = 2.1 × 10 −4 ) and OS (p = 5.8 × 10 −5 ). Conclusion: The erlotinib/O-desmethyl-erlotinib metabolic ratio reflecting the individual metabolic activity of erlotinib correlated with the severity of skin rash and outcome in patients treated with EGFR tyrosine kinase inhibitors. The metabolic ratio determined in serum may be used for therapeutic monitoring in erlotinib treatment and decisions on individual dosing to rash in rash-negative patients. Highlights: Severity of skin rash was associated with treatment outcome in terms of progression free survival (PFS) and overall survival (OS) in cancer patients treated with tyrosine kinase inhibitors. Drug-metabolising activity assessed by the erlotinib/O-desmethyl-erlotinib metabolic ratio was observed to be correlated with the severity of skin rash in that way that high metabolic activity lowers the occurrence of skin rash. The erlotinib/O-desmethyl-erlotinib metabolic ratio was also highly associated with PFS and OS in cancer patients. The individual metabolic activity of erlotinib determined in serum may be helpful for therapeutic monitoring in erlotinib treatment and decisions on individual dosing to rash in rash-negative cancer patients.